MEASUREMENT AND DISCLOSURE OF FINANCIAL INSTRUMENTS IN COMMERCIAL BANKS IN THE IRAQI ENVIRONMENT AND INTERNATIONAL FINANCIAL REPORTING STANDARDS (A COMPARATIVE STUDY) - Milad Hilal Hamo; Prof. Dr. Khawla H. Hamdan (Scholar Express Journals, 2023)
The accounting measurement and disclosure requirements for financial investments in the Iraqi environment differ from the international financial reporting standards, as accounting recognition under local accounting rules requires conditions and events that differ from those required by international standards, and the adoption of international financial reporting standards leads to the possibility of comparison between the financial statements of companies to serve Many parties, including investors, in making their investment decisions. The research aims to identify the nature of financial instruments in accounting thought and to identify differences in measurement and disclosure of financial instruments according to local accounting rules and the unified accounting system for banks and insurance companies on international financial reporting standards. Recommendations, the most important of which are: The need for the Accounting and Supervisory Standards Board in the Republic to adopt the International Financial Reporting Standards for Financial Instruments (IFRS 9) and (IFRS 7), taking into account the Iraqi environment.
Keywords: measurement and disclosure; financial instruments